Nilai-nilai Pendidikan Karakter dalam Gerak Dasar Tari Kejei Bagi Anak Usia Sekolah Dasar - Jauhari Kumara Dewi (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Education is one of leading sectors in the development of student character. Specifically, it aims to identify character values and integrate them into elementary school’s life. Kejei dance is one of the dances in which there are character values that have a role in shaping elementary school students’ character with God, themselves, others, and their nationality which expressed in every movement of the Kejei dance. The purpose of this study was to discover the meaning contained in the various basic movements of the Kejei dance in the process of shaping elementary students’ character. This research belonged to qualitative research with a narrative approach. Primary data sources are taken from observing the variety of movements of the Kejei dance. In other words, the data were collected through observation and interviews. Afterwards, the data gathered were analyzed through data reduction and conclusions. The results showed that the Kejei dance contains the meaning and value of character education which is reflected in several types of movements including Sembah Menari movement, Bederap Salah Pinggang movement, Metik Jari movement, Mateak Dayung movement, Sembah Penyudo movement, and Mendayung movement. In sum, the overall meanings of the basic movements of the Kejei dance show religious values, tolerance, discipline, and communication.